Floristic Diversity of Jammu and Kashmir, India, Especially in Context to Skin Care - Nisreen Husain*, Touseef Hussain Trak, Deepti Chauhan (International Journal of Advanced Science and Technology, 2020)
Objective: Jammu and Kashmir (J&K) is the Crown state of India, well known for its scenic beauty, ethnic cultures and floristic diversity. The present work was carried out with the aim to explain the complex relationships between traditional cultures and medicinal plants of the state. It deals with focusing primarily on the common skin ailments in J&K, and the inventory of some of the medicinal plants used in the treatment of skin disorders, depicting the floristic diversity of the state, especially of concern in skin care. Methodology: Field work and survey methods were used for the study. Also the women between the age of 30-50 years from different villages were interviewed. The relevant knowledge gathered about skin diseases and their cure with herbal and floristic species, from the local informants and different ethnic groups enabled our work to proceed in the right direction. Results: This study provides information about the floristic diversity of J&K, especially the ones used for skin care commonly. About 100 such species have been indicated in our work. In sum, the results emphasis on overall 6 aspects of our study. Firstly, an inventory of 100 skin care plants from J&K was prepared pointing out some of their basic characteristic details. Secondly, the range of family dominance for these plants was focused, followed thirdly, by their habit- based category. Frequently used different plant-parts of the plants considered in the inventory, used as medicines for skin treatment is also indicated as the fourth aspect of our work. The next and the fifth aspect is the survey about the known skin ailments of common occurrence in the study area. Lastly, the threatened species amongst the surveyed 100 plants has also been brought to notice. All the more, to enhance the authenticity, our study covered 8 major districts of J&K. Conclusion: The information about the common skin problems in J&K could be gathered more accurately. Floristic diversity focused with the use of different plants and herbs for skin care among the tribal communities and women in general, will be beneficial for mankind. Its importance on pharmaceutical, therapeutical and cosmeceutical fields will be enhanced, thereby influencing the society and the economic status.